Fate of the Fontan connection: Mechanisms of stenosis and management. (25th February 2019) - Hagler, Donald J.; Miranda, William R.; Haggerty, Brielle J.; Anderson, Jason H.; Johnson, Jonathan N.; Cetta, Frank; Said, Sameh M.; Taggart, Nathaniel W.
Abstract: Background: Stenosis of the venous connections and conduits is a well‐known late complication of the Fontan procedure. Currently, data on the outcomes of percutaneous intervention for the treatment of extra‐ or intracardiac conduits and lateral tunnel baffles obstruction are limited. In an attempt to better define the nature and severity of the stenosis and the results of catheter interventional management, we reviewed Fontan patients with obstructed extra‐ or intracardiac conduits and lateral tunnel baffles. Methods: Retrospective review of all Fontan patients who had cardiac catheterization from January 2002 to October 2018 was performed. Hemodynamic and angiographic data that assessed extra‐ or intracardiac conduit, or lateral tunnel baffle obstruction/stenosis were evaluated. Results: Twenty patients underwent catheter intervention because of conduit stenosis, including calcified homografts, stenotic Gore‐Tex conduits and obstructed lateral tunnels. Six other patients had Fontan obstruction but were referred for surgical revision. After stenting, there was a significant reduction in the connection gradient [2.0 mm Hg (IQR 2; 3) vs 0 mm Hg (IQR 0; 1), P < .0001]. Fontan conduit/connection diameter increased [10.5 mm (IQR 9; 12) vs 18 mm (IQR 14.9; 18); P < .0001] and New York Heart Association class [III (IQR II; III) vs I (IQR II; III); P = .03) with stent placement. Conclusions: We demonstrated the hemodynamics and angiographic subtypes of conduit stenosis in patients after Fontan, We showed that calcified homografts, stenotic Gore‐Tex conduits and lateral tunnels pathways can be safely and effectively stented to eliminate obstruction. Percutaneous stenting is associated with a decrease in connection gradients and improvement in functional capacity.